Enhanced Wide‐Angle Energy Conversion Using Structure‐Tunable Waveguide Arrays as Encapsulation Materials for Silicon Solar Cells. Issue 2 (18th December 2018) - Biria, Saeid; Chen, Fu‐Hao; Hosein, Ian D.
Abstract : The authors report on the enhancement in optical energy conversion in silicon solar cells encapsulated with a polymer film comprising of waveguide array structures. The structures are fabricated through light‐induced self‐writing with periodic arrangements of optical beams transmitted through a binary component photopolymer, wherein a periodic core‐cladding architecture is produced. The size, spacing, and arrangement of the cores are varied through the size and arrangement of the optical beams via photomask design. A range of waveguide array structures are produced using different masks and component weight fractions. External quantum efficiency (EQE) measurements reveal structures that provide the greatest enhancement for normal and non‐normal incidence irradiation, the latter for which reveals wide‐angle light capture and conversion. Encapsulated solar cells yield an approximate 10% enhancement in EQE and a 20% increase in the short circuit current, up to an incident angle of 40°, as compared to uniform encapsulants. The experimental results are corroborated by beam propagation simulations that show the spatial confinement of transmitted optical energy is the main effect that increases conversion efficiency. Principles that establish a structure‐property‐performance relationship are discussed, toward rational materials processing to increase energy conversion. Abstract : Broadband waveguide array structures are inscribed in polymer films as encapsulation materials for solar cells to increase energy conversion at wide incident angles. The structure is tuned in terms of waveguide diameter, array spacing, and symmetry. Conversion efficiency and output current are increased, especially at wide incident angles, enabled by the structure's capability to collect and transmitt light toward the solar cell.